Pelatihan Penulisan Artikel ilmiah pada Prosiding dan Jurnal Nasional untuk mahasiswa di Wilayah Bodetabek - Riyan - Arthur; Daryati; Supriyadi (Lembaga Penelitian dan Pengabdian Kepada Masyarakat, 2022)
The purpose of this activity is to improve students' ability to write scientific articles. Training and mentoring is carried out to improve students' ability to write scientific articles in journals and proceedings nationwide. This activity was conducted online using Zoom media and Youtube Education channel. Training and mentoring time from June 7 to October 30, 2020. Methods used are lectures, discussions, q&A and assignments online. This training was attended by 1,476 participants from various professions, but the target remains on students in bodetabek area. Training and devotion results show the average student's ability tends to be good at a score of 84.05 with some students reaching a score of 100, although some still score below 70